Effect of Workload and Position Mutations on Performance with Work Motivation as An Interverning Variable at Bintara Polri Polres West Lombok - I Kadek Anom Suardinatha; I Gede Putu Kawiana; Putu Herny Susanti (International Journal of Social Science, Education, Communication and Economics (SINOMICS JOURNAL), 2023)
The purpose of this study was to determine and analyze the effect of workload and job transfers on performance with work motivation as an interverning variable at Bintara Polri Polres Lombok Barat. The research population was members of the West Lombok Police and Sub Satker (Polsek) of 808 people. The technique of determining the sample used purposive sampling so that 89 people were obtained as respondents. The research instrument used questionnaires as well as several other data collection methods such as observation, interviews and literature and analysis methods using descriptive analysis and inferential analysis with Structural Equation Model-Partial Least Square (SEM-PLS) analysis. The results showed that workload had a negative effect and significant to performance, position mutations have a positive and significant effect on performance, workload has a negative and significant effect on work motivation, position mutations have a positive and significant effect on work motivation, work motivation has a positive and significant effect on performance, workload has a negative and significant effect on performance with motivation as an intervening variable and position mutations have a positive effect on performance with motivation as an intervening variable at Bintara Polri Polres Lombok Barat. The implication of the research is the need for an evaluation in assigning tasks to members in order to maintain performance results and transfer of positions at Bintara Polri Polres Lombok Barat needs to be carried out regularly in order to improve the performance of members and eliminate feelings of boredom in carrying out tasks both at Satker Polres Lombok Barat and Sub Satker (Polsek).